Recent advances in waste-derived functional materials for wastewater remediation - Zhijie Chen; Wei Wei; Hong Chen; Bing-Jie Ni (Eco-Environment & Health, 2022)
Water pollution is a major concern for public health and a sustainable future. It is urgent to purify wastewater with effective methods to ensure a clean water supply. Most wastewater remediation techniques rely heavily on functional materials, and cost-effective materials are thus highly favorable. Of great environmental and economic significance, developing waste-derived materials for wastewater remediation has undergone explosive growth recently. Herein, the applications of waste (e.g., biowastes, electronic wastes, and industrial wastes)-derived materials for wastewater purification are comprehensively reviewed. Sophisticated strategies for turning wastes into functional materials are firstly summarized, including pyrolysis and combustion, hydrothermal synthesis, sol–gel method, co-precipitation, and ball milling. Moreover, critical experimental parameters within different design strategies are discussed. Afterward, recent applications of waste-derived functional materials in adsorption, photocatalytic degradation, electrochemical treatment, and advanced oxidation processes (AOPs) are analyzed. We mainly focus on the development of efficient functional materials via regulating the internal and external characteristics of waste-derived materials, and the material’s property-performance correlation is also emphasized. Finally, the key future perspectives in the field of waste-derived materials-driven water remediation are highlighted.